Pengaruh Volume Perdagangan, Earning Volatility, Firm Size, dan Order Imbalance terhadap Volatilitas Harga Saham - Cahyani, Yenni; Hidayah, Wulan Nur (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
This study aims to determine the effect of trading volume, earning volatility, firm size, and order imbalance on stock price volatility in companies listed in the IDX30 index on the Indonesia Stock Exchange. The data used is secondary data and the method used is panel data regression analysis with the help of the Eviews 12 program to obtain a comprehensive picture of the relationship between one variable and another. The sample in this study consisted of 14 companies that were consistently listed on the IDX30 for 5 years from 2019-2023 with purposive sampling as the sampling method. The results of this study are that the variables of Stock Trading Volume, Firm Size and Order Imbalance partially have an influence on Stock Price Volatility. While Earning Volatility partially has no effect on Stock Price Volatility. The results of simultaneous regression analysis obtained that Stock Trading Volume, Earning Volatility, Firm Size, and Order Imbalance together (simultaneously) affect Stock Price Volatility.